PENGGUNAAN COOPERATIVE LEARNING TIPE JIGSAW DALAM MENINGKATKAN INTERAKSI EDUKATIF DAN HASIL BELAJAR IPS - Melliana, Melliana; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThe problem in this research is "Whether by using cooperative learning Jigsaw type can improve Educational Interaction and Social Science Learning Class III SD Negeri 14 Bengkayang". This study aims "To improve the results of educational interaction and student learning outcomes by using Jigsaw type in third grade students of State Elementary School 14 Bengkayang. This research is a classroom action research and is collaborative. The place of research took place at State Elementary School 14 Bengkayang with the subject of research that is the third grade students, amounting to 30 people. Technique of collecting data that is used is direct observation technique with data collecting tool that is IPKG I and IPKG II sheets. This research is done for 2 cycles. The results of the study implementation design obtained average on the first cycle of 2.70, cycle II of 3.84, The results of the learning implementation obtained on average in the first cycle of 2.95, cycle II of 3.82, Interaction educative in IPS learning using jigsaw type increased for students who asked questions to teachers by 20% from cycle I to cycle II, there was an increase for students who asked questions to other students of 16.67% from cycle I to cycle II, an increase for students who answer the questions of teachers amounted to 16.66% from cycle I to cycle II, and an increase for students who gave opinions when the discussion of 15.67% from cycle I to cycle II, the results of the study of student learning outcomes obtained average in the first cycle of 63.67, the second cycle of 84.00. Thus, research through Cooperative Learning Jigsaw Type Learning can improve educational interaction and social science learning outcomes. Keywords: Improvement, Cooperative Learning Jigsaw Type, Educational Interaction,                   Learning Outcomes, Social Sciences.